Chemico-technological parameters and maturation curves of sweet sorghum genotypes for bioethanol production - Freita, Lidyane Aline de [UNESP]; Costa, Gustavo Henrique Gravatim [UNESP]; Masson, Igor dos Santos [UNESP]; Ferreira, Osania Emerenciano [UNESP]; Mutton, Miguel Angelo [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (Academic Journals, 2014)
The sweet sorghum has high potential for bioethanol production, especially for using the same industrial production complex and for being processed during sugarcane off-season. The objective of this study was to evaluate the chemico-technological characteristics of the following sorghum genotypes: CVSW80007, CVWS80147, and BRS610, which were grown in Jaboticabal – São Paulo, State, Brasil. The experimental design used was a completely randomized block in a split-split-plot desing. The main treatments were three genotypes, two stalk management systems (stalks with and without leaves and panicles), and the tertiary treatment were six harvesting times (100, 105, 110, 118, 135, and 160 days after sowing) with three replications. The soluble solids content (Brix), total reducing sugars (TRS), pH, total acidity, total phenolic compounds, and starch content of the juice extracted were evaluated. The results indicated that given the chemico-technological characteristics of the genotypes CVWS80147 and CVSW80007, they can be used as raw material for bioethanol production, with useful-period-of-industrialization (UPI) about 40 days, starting at 110 days after sowing. The better results with chemical-technological parameters is find at 118 to135 days after sowing.
Keywords: Sorghum bicolor; Technological quality; Productivity; Biometrics; Bioethanol